CO/CO and NO/NO coupling at a hidden frustrated Lewis pair template. Issue 3 (19th January 2017) - Wang, Tongdao; Wang, Long; Daniliuc, Constantin G.; Samigullin, Kamil; Wagner, Matthias; Kehr, Gerald; Erker, Gerhard
Abstract : The reversible enamine/HB(C6 F5 )2 Lewis adduct reacts with CO by selective head to tail coupling whereas it reacts with NO via a vicinal N/B Lewis pair to give a head to head NO/NO coupling product. Abstract : N -Allyltetramethylpiperidine is readily isomerized to the corresponding enamine by treatment with catalytic amounts of B(C6 F5 )3 . It adds HB(C6 F5 )2 at the nucleophilic enamine carbon atom to form a C/B Lewis adduct. This reacts with two molar equivalents of carbon monoxide by selective head to tail coupling to give a five-membered C2 O2 B heterocycle. In contrast the enamine/HB(C6 F5 )2 Lewis pair reacts with two molar equiv. of nitric oxide by head to head coupling. This reaction probably proceeds via equilibrium with the corresponding vicinal N/B Lewis pair. Most products were characterized by X-ray diffraction.